Division of the role and physiological impact of multiple lysophosphatidic acid acyltransferase paralogs - Takuya Ogawa; Misaki Kuboshima; Nittikarn Suwanawat; Jun Kawamoto; Tatsuo Kurihara (BMC Microbiology, 2022)
Abstract Background Lysophosphatidic acid acyltransferase (LPAAT) is a phospholipid biosynthesis enzyme that introduces a particular set of fatty acids at the sn-2 position of phospholipids. Many bacteria have multiple LPAAT paralogs, and these enzymes are considered to have different fatty acid selectivities and to produce diverse phospholipids with distinct fatty acid compositions. This feature is advantageous for controlling the physicochemical properties of lipid membranes to maintain membrane integrity in response to the environment. However, it remains unclear how LPAAT paralogs are functionally differentiated and biologically significant. Results To better understand the division of roles of the LPAAT paralogs, we analyzed the functions of two LPAAT paralogs, PlsC4 and PlsC5, from the psychrotrophic bacterium Shewanella livingstonensis Ac10. As for their enzymatic function, lipid analysis of plsC4- and plsC5-inactivated mutants revealed that PlsC4 prefers iso-tridecanoic acid (C12-chain length, methyl-branched), whereas PlsC5 prefers palmitoleic acid (C16-chain length, monounsaturated). Regarding the physiological role, we found that plsC4, not plsC5, contributes to tolerance to cold stress. Using bioinformatics analysis, we demonstrated that orthologs of PlsC4/PlsC5 and their close relatives, constituting a new clade of LPAATs, are present in many γ-proteobacteria. We also found that LPAATs of this clade are phylogenetically distant from principal LPAATs, such as PlsC1 of S. livingstonensis Ac10, which are universally conserved among bacteria, suggesting the presence of functionally differentiated LPAATs in these bacteria. Conclusions PlsC4 and PlsC5, which are LPAAT paralogs of S. livingstonensis Ac10, play different roles in phospholipid production and bacterial physiology. An enzyme belonging to PlsC4/PlsC5 subfamilies and their close relatives are present, in addition to principal LPAATs, in many γ-proteobacteria, suggesting that the division of roles is more common than previously thought. Thus, both principal LPAATs and PlsC4/PlsC5-related enzymes should be considered to decipher the metabolism and physiology of bacterial cell membranes.